2020
DOI: 10.2147/cmar.s278382
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nomogram Including Elastography for Prediction of Contralateral Central Lymph Node Metastasis in Solitary Papillary Thyroid Carcinoma Preoperatively</p>

Abstract: Background It is controversial whether contralateral prophylactic central neck dissection (PCND) should be performed for patients with solitary and clinical lymph node negative (cN 0 ) papillary thyroid carcinoma (PTC) although routine ipsilateral PCND is required. Objective The aim of this study was to develop an improved nomogram including clinical features, ultrasound, and acoustic radiation force impulse (ARFI) elastography for the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Contralateral central lymph node dissection for unilateral PTC is controversial, mainly because of its low metastasis rate, and the occurrence of complications such as hypoparathyroidism and recurrent laryngeal nerve injury. Therefore, some scholars have looked for predictors of contralateral central cervical lymphatic metastasis [13,25].Han et al, create a prediction model for contralateral central cervical lymphatic metastases in unilateral PTC [26]. Kim et al suggested that ipsilateral central lymphatic metastasis could predict contralateral central lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contralateral central lymph node dissection for unilateral PTC is controversial, mainly because of its low metastasis rate, and the occurrence of complications such as hypoparathyroidism and recurrent laryngeal nerve injury. Therefore, some scholars have looked for predictors of contralateral central cervical lymphatic metastasis [13,25].Han et al, create a prediction model for contralateral central cervical lymphatic metastases in unilateral PTC [26]. Kim et al suggested that ipsilateral central lymphatic metastasis could predict contralateral central lymphatic metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…PTC is prone to central lymph node metastasis. Central lymph nodes can be divided into ipsilateral central lymph nodes and contralateral central lymph nodes [12].Routine prophylactic central lymph node dissection is required [2].However, for unilateral cancer, the dissection of the contralateral central lymph node is controversial, mainly because of low metastasis rate and postoperative complications [13,14].For PTC with N1b, there are few studies on contralateral central lymph node dissection of unilateral cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There remains an existing need for improved CLNM prediction performance. Current studies have established a prediction model using a regression algorithm and nomogram, making it possible to forecast CLNM risk in clinical application (14)(15)(16). Machine learning (ML) algorithms have also been widely used in image diagnosis over the last few years.…”
Section: Introductionmentioning
confidence: 99%
“…It was recognized that there remains an existing need for improved CLNM prediction performance. Available studies have established the prediction model by regression algorithm and nomogram, making it possible to forecast CLNM risk in clinical application [14][15][16]. Machine learning (ML) algorithm has been widely used in image diagnosis over the last few years.…”
Section: Introductionmentioning
confidence: 99%